2017
DOI: 10.3347/kjp.2017.55.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Human Cases of Fascioliasis in Fujian Province, China

Abstract: Fascioliasis is a foodborne zoonotic parasitic disease. We report 4 cases occurring in the same family, in whom diagnosis of acute fascioliasis was established after series of tests. One case was hospitalized with fever, eosinophilia, and hepatic lesions. MRI showed hypodense changes in both liver lobes. The remaining 3 cases presented with the symptom of stomachache only. Stool analysis was positive for Fasciola eggs in 2 adult patients. The immunological test and molecular identification of eggs were confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…In this study, no change in the value of AFP and CEA was observed for all the rabbit sera. Our data are in agreement with previous case reports indicating that tumor markers including AFP and CEA were at normal value in human fascioliasis [ 1 , 14 , 15 , 28 ]. This suggested that there might be no relationship between fascioliasis and cholangiocarcinoma, at least at the acute phase.…”
supporting
confidence: 93%
“…In this study, no change in the value of AFP and CEA was observed for all the rabbit sera. Our data are in agreement with previous case reports indicating that tumor markers including AFP and CEA were at normal value in human fascioliasis [ 1 , 14 , 15 , 28 ]. This suggested that there might be no relationship between fascioliasis and cholangiocarcinoma, at least at the acute phase.…”
supporting
confidence: 93%
“…A prevalence of 0.011% was reported in the national survey conducted in 1988–1992, with cases found in eight provinces [56], while it decreased to 0.0007% in the national survey done in 2014–2015 [51]. Although the overall prevalence is very low, several outbreaks have been reported recently [55, 57]. The low awareness of this infection in the public usually leads to severe delays in the diagnosis and subsequent management of the disease.…”
Section: Progress In the Control And Elimination Of Ntds In The Peoplmentioning
confidence: 99%
“…The infection may also be acquired through consumption of water contaminated by encysted metacercaria, or food items washed with such water (Ibrahim 2017 ) or consumption of contaminated water of human sewage (Aleixo et al 2015 ). According to the World Health Organization (WHO), human fasciolosis is classified as a Neglected Tropical Disease (NTD) (Ai et al 2017 ; Abah et al 2019 ). Human fasciolosis is a major public health problem in several areas of the world, with human cases being increasingly reported from Europe, the Americas, Oceania, India and Africa (Aksoy et al 2005 ; Soliman 2008 ).…”
Section: Introductionmentioning
confidence: 99%